Laser Marking Writing Analysis Using a Character Detection Camera to View Marking Results - Nanda, Rizki Aulia; Karyadi; Mulyadi, Dodi; Supriyanto, Agus; Suhara, Ade; Rizki, Muhammad Nuzan (E-Journal Universitas Malikussaleh, 2025)
Laser marking has become an industrial trend to label a product to avoid problems arising from errors in product placement, labels can also be other markers depending on needs, laser marking can provide good writing prints on steel sheets. However, problems arise due to poor parameter input errors resulting in marking reading results that cannot be read by the scanner machine, this study aims to provide an analysis of the influence of laser marking input variations that can provide good marking quality, to determine the quality of marking, researchers use a Logitech camera assisted by Open CV programming, to see the quality of laser marking results that can be read by the scanner. This research method begins with inputting 6 parameter variations including speed, laser power and laser frequency, then Open CV programming is carried out to obtain image reading quality with color and line recognition, the reading results will automatically display the error level of the study. The results of the study explain the first test with a high error rate due to low input variables so that the reading is not clear, while the error value is 104040 in color recognition and 69024 in lines that are read with a 100% end range. The lowest error value is in the second test with the highest input variable, namely 1309 in black and white color recognition and 1345 in lines with a range of 100%, therefore the sixth test can be read clearly and well.